UMPSA is 5th best in the world for SDG #1 No Poverty - Mimi Rabita, Abd Wahit (UMPSA, 2024)
PEKAN, 1 July 2024 - Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) is ranked 201-300 in the world’s best and fifth in the world’s best in Sustainable Development Goal 1: No Poverty on the university’s efforts to reach out to the local community and help to ease the burden on the families of students in need.